PERTUMBUHAN KARAKTER PANCA JIWA SANTRI MELALUI METODE TARGHIB WA TARHIB DI PONDOK PESANTREN DAARUL UKHUWAH AS’ADIYAH KABUPATEN KUTAI KARTANEGARA - Hamsir, Hamsir; Khojir, Khojir; Shafa, Shafa (Inspiratif Pendidikan, 2023)
This research examines the application of the Targhib wa Tarhib method in understanding the character growth of students at Daarul Ukhuwah As’adiyah Islamic Boarding School. This study uses a qualitative type of field research. Sources of research data were obtained from interviews, observations, and documentation from the field at Daarul Ukhuwah As’adiyah Islamic Boarding School. The approach used in this research is a case study approach. The results of this study indicate that the application of the Targhib wa Tarhib method has a significant role in cultivating the five-soul character at the Daarul Ukhuwah As’adiyah Islamic Boarding School. There are several factors that influence the growth of the five soul characters, namely a conducive educational environment, the role of a good educator, positive social interaction, understanding and awareness of religious values, as well as family and community support. There are also supporting factors in the application of the Targhib wa Tarhib method including the existence of a conducive educational environment, the role of a good educator, the use of appropriate reinforcement, an emphasis on gentleness in educating, and consistency in the application of the method. However, there are also inhibiting factors, such as disproportionate punishments, lack of understanding and awareness of the importance of building the five souls character, and lack of support from the educational environment and family.